Risk factors of post-traumatic stress disorder post partum: a scoping review - Sitti Kutria; Rosmita Nuzuliana; Nurul Kurniati (International Journal of Health Science and Technology, 2021)
Post-traumatic stress disorder (PTSD) is a condition after giving birth, the situation is the main cause result in psychological stress which is characterized to hallucinate, memory disturbances, avoidance, and excessive alertness. This study, identify scientific and clinical views of the results of previous studies, to provide a baseline in identifying the factors that cause traumatic events after childbirth. The method used is a scoping review which consists of 5 stages, namely: focus review, conducting a literature search, determining several relevant studies, conducting critical assessments, tracing various data, analyzing and reporting results. PRISMA flowchart (Optional Reporting Items for Systematic and Meta-analysis) was used in the literature search. 12 selected literature and graded (A). The results showed that there are several factors that cause symptoms of PTSD after childbirth including cesarean delivery, service by health workers, previous experience of childbirth history and women having a history of psychosocial disorders.